Nanoscaled Metamaterial as an Advanced Heat Pump and Cooling Media. Issue 2 (14th April 2016) - Levchenko, Igor; Beilis, Isak I.; Keidar, Michael
Abstract : Major characteristics of the nanoscaled high‐temperature metamaterial capable of reversal heat transmission are calculated, and two design variants are proposed and discussed. Specifically, the basic design has been proposed involving the solid‐state highly emissive cathode material, and the modification with a liquid‐state emissive material (e.g., cesium) filling the nanoporous structure such as previously synthesized alumina membrane or nanobottle structure. The performance characteristics of the proposed metamaterial have also been analyzed based on the three electron emission materials typical for the low‐, medium‐, and high‐temperature emission regimes. The geometrical size, temperature ranges, powers, cooling efficiency, and performance factors of the considered design are examined. In particular, it has been demonstrated that the working potential difference reached 2–10 V at the current density 100 A cm −2 and interelectrode distance ranging from 3 to 10 μm. The electron cooling efficiency determined as the ratio of a heat flux taken off the cathode by the emitted electrons to the total heat flux to the cathode surface from the interelectrode space can reach 10 −25, depending on cathode material and temperature, with the coefficient of performance reaching 8 when the cathode and anode materials are sophisticatedly selected. The future trends in the development of nanoscaled high‐temperature metamaterial are discussed. Abstract : A novel nanoscaled, high‐temperature metamaterial capable of reversal heat transmission is justified analytically, and the advanced design variants are examined. Performance characteristics of the metamaterial are calculated as functions of geometrical size, temperature ranges, power, and materials used. The future trends in the development of such a metamaterial are discussed.